Java All-in-One For Dummies, 4th Edition - Lowe, Doug (For dummies, 2014)
Everything you need to get going with Java!Java All-in-One For Dummies, 4th Edition has what you need to get up and running quickly with Java. Covering the enhanced mobile development and syntax features as well as programming improvements, this guide makes it easy to find what you want and put it to use.Focuses on the vital information that enables you to get up and running quickly with JavaCovers the enhanced multimedia features as well as programming enhancements, Java and XML, Swing, server-side Java, Eclipse, and moreMinibooks cover Java basics; programming basics; strings, arrays, and collections; programming techniques; Swing; Web programming; files and databases; and a "fun and games" categoryJava All-in-One For Dummies, 4th Edition focuses on the practical information you need to become productive with Java right away.